Factors Shaping Students Attitudes Toward Sharia Economics: an Empirical Study in Jakarta - Prijanto, Budi; Sari, Agustin Rusiana; Azifah, Nur (Riwayat: Educational Journal of History and Humanities, 2025)
This study investigates the factors influencing high school students' attitudes toward choosing Sharia Economics as a field of study in Jakarta. Guided by the Theory of Planned Behavior (TPB), the research examines the roles of subjective norms, perceived behavioral control, religiosity, and career perception in shaping student attitudes. Using a quantitative approach and data from 120 students, multiple linear regression analysis revealed that all four factors significantly impact students attitudes, explaining 53.4% of the variance. Career perception emerged as the most influential variable, followed by religiosity, subjective norms, and perceived behavioral control. The findings highlight the importance of aligning religious values, career prospects, and social support to foster interest in Sharia Economics. The study suggests that promoting Islamic economics education should involve strategic efforts in career counseling, religious integration, and resource accessibility